The theoretical foundations of criminology: place, time and context - Mooney, Jayne (Routledge, 2020)
"Written from a critical perspective, this book brings criminological theory to life. It presents the core theories of criminology as historical and cultural products and theorists as producers of culture located in particular places, writing in specific historical periods and situated in precise intellectual networks and philosophical controversies. This book illustrates that theory does not arise 'out of the blue' and highlights the importance of understanding how and why ideas emerge at certain points in time, why they gained currency, and the influence that they have had. It follows the trajectory of criminology from pre-Enlightenment society through to the present day and the proliferation of criminological thinking. It explores: - early concepts of justice in continental Europe from the 14th to mid-18th centuries, - the impact of the Enlightenment and the origins of classicist criminology, - the development of positivism within criminology and its role in 'othering', - the Chicago School of Sociology, - the development of a sociological criminology, - feminist theory and criminology, - and the emergence of critical criminology. Theoretical Foundations of Criminology provides an invaluable contribution to the growing conversation over criminology's 'origin story' and the level that this is grounded in the idiosyncrasies of the North Atlantic world and its historical development. This book will be invaluable reading to students and academics engaged in studies of criminology and criminal justice"--